Metastasized pancreatic neuroendocrine tumor in a teenage girl: a case report - Tremmel, Tina; Holland-Cunz, Stefan; Günther, Patrick (Journal of medical case reports, 2015)
Metastasized pancreatic neuroendocrine tumors are extremely rare malignancies, especially in children. Therefore, therapeutic options are limited, and few standardized therapy regimens exist.